1975
DOI: 10.1111/j.1600-0609.1975.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Platelets in the Precipitation of Soluble Fibrin by Endotoxin

Abstract: This study is intended to clarify whether or not platelets are essential to endotoxin‐induced precipitation of soluble fibrin representing the second phase of microclot formation. Renal glomerular microclots could be observed in extremely thrombocytopenic rabbits to the same extent as in normal rabbits after the injection of endotoxin into animals with circulating soluble fibrin. Thrombocytopenia was induced by feeding rabbits busulphan, and soluble fibrin was produced by infusing ancrod. The experiments indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In contrast, coarse fibrinous microthrombi which do not show any platelet inclusions, but are exclusively composed of period-coincidentally aggregated clumsy fibrillar bundles, without signs of a trellis pattern, are generated from a primary precipitation of soluble intermediates of the fibrinogen-fibrin conversion under the conditions of prestasis or stasis. Without doubt, this formation does not depend on the participation of platelet aggregates, but also occurs in thrombocytopenic test animals [26]. The morphogenesis of these coarse, primary fibrinous microthrombi parallels the morphogenesis of highly polymerized fibrinous clots in the test tube.…”
Section: Coarse Hyaline Microthrombimentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, coarse fibrinous microthrombi which do not show any platelet inclusions, but are exclusively composed of period-coincidentally aggregated clumsy fibrillar bundles, without signs of a trellis pattern, are generated from a primary precipitation of soluble intermediates of the fibrinogen-fibrin conversion under the conditions of prestasis or stasis. Without doubt, this formation does not depend on the participation of platelet aggregates, but also occurs in thrombocytopenic test animals [26]. The morphogenesis of these coarse, primary fibrinous microthrombi parallels the morphogenesis of highly polymerized fibrinous clots in the test tube.…”
Section: Coarse Hyaline Microthrombimentioning
confidence: 84%
“…On one hand, soluble fibrinogen-fibrin monomer complexes are looked upon as the morphologic equivalent of a plasmatic hypercoagulability. On the other hand, high molecular weight fibrin degradation products are symptoms of a plasmin-induced fibrin olysis [26,49,54,71]. Like fibrinogen, high-molecular weight degradation products may aggregate with plasmatic fibrin monomers in vivo and in vitro and form soluble fibrin monomer-fibrin degradation product complexes.…”
Section: Fibrin Monomer and Fibrin Oligomermentioning
confidence: 99%
“…The release of these precipitating factors can be induced by endotoxin in vitro as well as in vivo. Experiments in the rabbit, however, have shown that platelets are not involved in the precipitation of soluble fibrin mediated by endotoxin, as thrombocytopenia did not prevent the occurrence of microclot formation [37,176]. Thrombocytopenia was induced either by platelet antiserum or by busulphan (Table 9).…”
Section: (A) Platelets and Precipitation And/or Polymerization Of Solmentioning
confidence: 99%